Fecal Indicator Bacteria along Multiple Environmental Transmission Pathways (Water, Hands, Food, Soil, Flies) and Subsequent Child Diarrhea in Rural Bangladesh - Pickering, Amy J.; Ercumen, Ayse; Arnold, Benjamin F.; Kwong, Laura H.; Parvez, Sarker Masud; Alam, Mahfuja; Sen, Debashis; Islam, Sharmin; Kullman, Craig; Chase, Claire; Ahmed, Rokeya; Unicomb, Leanne; et al. (American Chemical Society, 2019)
Enteric pathogens can be transmitted through multiple environmental pathways, yet little is known about the relative contribution of each pathway to diarrhea risk among children. We aimed to identify fecal transmission pathways in the household environment associated with prospectively measured child diarrhea in rural Bangladesh. We measured the presence and levels of Escherichia coli in tube wells, stored drinking water, pond water, child hand rinses, courtyard soil, flies, and food in 1843 households. Gastrointestinal symptoms among children ages 0–60 months were recorded concurrently at the time of environmental sample collection and again a median of 6 days later. Incident diarrhea (3 or more loose stools in a 24-h period) was positively associated with the concentration of E. coli on child hands measured on the first visit (incidence rate ratio [IRR] = 1.23, 95% CI 1.06, 1.43 for a log10 increase), while other pathways were not associated. In cross-sectional analysis, there were no associations between concurrently measured environmental contamination and diarrhea. Our findings suggest higher levels of E. coli on child hands are strongly associated with subsequent diarrheal illness rates among children in rural Bangladesh.